Impulse to act : a new anthropology of resistance and social justice - Alexandrakis, Othon (Indiana University Press, 2016)
What drives people to take to the streets in protest' What is their connection to other activists and how does that change over time' How do seemingly spontaneous activist movements emerge, endure, and evolve, especially when they lack a leader and concrete agenda' How does one analyze a changing political movement immersed in contingency' Impulse to Act addresses these questions incisively, examining a wide range of activist movements from the December 2008 protests in Greece to the recent chto delat in Russia. Contributors in the first section of this volume highlight the affective dimensions of political movements, charting the various ways in which participants coalesce around and belong to collectives of resistance. The potent agency of movements is highlighted in the second section, where scholars show how the emerging actions and critiques of protesters help disrupt authoritative political structures. Responding to the demands of the field today, the novel approaches to protest movements in Impulse to Act offer new ways to reengage with the traditional cornerstones of political anthropology.